A Golden Rule for Politics? - McCurry, Mike (2019)
The division, bitterness, and anger in American politics are remarkable. Civility seems to have evaporated, and there is often little or no respect between those who argue. To address this confrontational and mean-spirited public debate, this essay offers some "Golden Rules" for civil discourse, patterned after Jesus's commandments: "In everything do to others as you would have them do to you" (Matt 7:12) and "You shall love your neighbor as yourself" (Lev. 19:18; Matt 22:40; Mark 12:34).
Keywords: American; Civil discourse; Faith and politics; Golden Rule; Politics; Public debate; Sermon on the Mount